Advances in nanotechnology and the environmental sciences : applications, innovations, and visions for the future - Vakhrushev, Alexander V.; Ameta, Suresh C.; Susanto, Heru, 1965-; Haghi, A. K. (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2020)
"This volume showcases a selection of new research on nanotechnological applications for environmental protection along with new advanced technologies in nanochemistry. It presents an interdisciplinary approach that brings together materials science, chemistry, and nanotechnology. Part I of the volume looks at environmental topics that include an exploration of the challenges of the global water crisis and new technology in nanofiltration and water purification. It provides an informative overview of green nanotechnology, green nanomaterials, and green chemistry. Some of the advanced technologies discussed in Part II include the application of quantum dots, a nanochemical approach to using ICT technology, and new research on polymer nanocomposites as a smart material along with its synthesis, preparation, and properties. Other important topics are included as well. The volume provides an overview of the highlights and potential for future developments and applications in chemical engineering. The information presented here will be of interest to researchers and graduate students in chemistry, engineering, and materials science, and it will also be a useful guide for industry professionals. The volume aims to provide inspiration for scientists and new ideas for developers and innovators in industry."--
Nanotechnology for environmental protection -- Global water crisis, nanofiltration, the vast innovations, and the vision for the future / Sukanchan Palit -- Nanofiltration, nanotechnology, and chemical engineering science : the scientific truth and a vision for the future / Sukanchan Palit -- Water purification and nanotechnology : a critical overview and a vision for the future / Sukanchan Palit -- Green nanotechnology : an approach towards environment safety / Francisco Torrens and Gloria Castellano -- Green nanotechnology, green nanomaterials, and green chemistry : a far-reaching review and a vision for the future / Sukanchan Palit -- Advanced technologies -- Quantum dots and their applications / Rakshit Ameta, Kanchan Kumari Jat, Jayesh Bhatt, and Suresh C. Ameta -- Shifting nanochemistry to ICT technology : a cheminformatics approach / Heru Susanto -- Polymer nanocomposites, a smart material : synthesis, preparation, and properties / Sonia Khanna -- Theoretical bases of simulation of formation processes of nanostructures in a gas medium and results of numerical studies of nanosystems / A. Yu. Fedotov -- Carbon nanotubes as chemical sensors and biosensors : a review / Rakshit Ameta, Kanchan Kumari Jat, Jayesh Bhatt, Avinash Rai, Tarachand Nargawe, Dipti Soni, and Suresh C. Ameta -- Applications of micellear phase of pluronics and tetronics as nanoreactors in the synthesis of nobel metal nanoparticles / Rajpreet Kaur, Navdeep Kaur, Divya Mandial, Lavanya Tandon, and Poonam Khullar -- Methods for calculating the thermoelectric characteristics of nanomaterials / A. V. Severyukhin, O. Yu. Severyukhina, and A. V. Vakhrushev.
OCLC-licensed vendor bibliographic record.
Keywords: Environmental engineering -- Materials; Nanostructured materials; Nanotechnology -- Environmental aspects; Green chemistry; SCIENCE / General; SCIENCE / Life Sciences / Biology / Microbiology; TECHNOLOGY / Nanotechnology